MSRAformer: Multiscale spatial reverse attention network for polyp segmentation. (December 2022) - Wu, Cong; Long, Cheng; Li, Shijun; Yang, Junjie; Jiang, Fagang; Zhou, Ran
Abstract: Colon polyp is an important reference basis in the diagnosis of colorectal cancer(CRC). In routine diagnosis, the polyp area is segmented from the colorectal enteroscopy image, and the obtained pathological information is used to assist in the diagnosis of the disease and surgery. It is always a challenging task for accurate segmentation of polyps in colonoscopy images. There are great differences in shape, size, color and texture of the same type of polyps, and it is difficult to distinguish the polyp region from the mucosal boundary. In recent years, convolutional neural network(CNN) has achieved some results in the task of medical image segmentation. However, CNNs focus on the extraction of local features and be short of the extracting ability of global feature information. This paper presents a Multiscale Spatial Reverse Attention Network called MSRAformer with high performance in medical segmentation, which adopts the Swin Transformer encoder with pyramid structure to extract the features of four different stages, and extracts the multi-scale feature information through the multi-scale channel attention module, which enhances the global feature extraction ability and generalization of the network, and preliminarily aggregates a pre-segmentation result. This paper proposes a spatial reverse attention mechanism module to gradually supplement the edge structure and detail information of the polyp region. Extensive experiments on MSRAformer proved that the segmentation effect on the colonoscopy polyp dataset is better than most state-of-the-art(SOTA) medical image segmentation methods, with better generalization performance. Reference implementation of MSRAformer is available at https://github.com/ChengLong1222/MSRAformer-main . Highlights: Propose a new model MSRAformer for polyp segmentation. Introduce Swin Transformer and designed as a pyramid encoder. Propose a new multiscale channel attention mechanism. Propose a simple and effective spatial attention mechanism.